Tabu Search- and Conservation Voltage Reduction-Based Service Restoration Algorithm for Cold Load Pickup Conditions - Widiputra, Victor; Jung, Jaesung (Journal of electrical engineering & technology, 2020)
Cold load pickup (CLPU) has become a major concern for distribution systems as the use of thermostatically controlled devices continues to increase. CLPU reduces load diversity, which thus increases the total load on the system. Without a sufficient supply, the system must be divided into sections and sequentially restored to prevent system overload, which can lead to a second blackout. This paper presents a service restoration strategy that optimizes the sequence of section restoration to minimize the total restoration time without additional generation in the system. The search for the optimum combination of restored sections is performed by implementing Tabu Search (TS). The CLPU effects are mitigated by using conservation voltage reduction (CVR). The power consumption of the load will decrease, which allow more load sections to be connected without overloading the system. To verify the algorithm, two simulations were performed. The first simulation compares the performance of the proposed algorithm to that of the greedy algorithm. The second simulation demonstrates the superior ability of the proposed algorithm to maintain an acceptable operating voltage during the restoration process.